Integrasi PAI dengan pluralisme dan multikulturalisme - Norjamilah; Normuslim; Hamdanah (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The diversity of Indonesian society in terms of religion, culture, ethnicity, and language demands an education system that is able to foster an inclusive, tolerant, and fair attitude in differences. Islamic Religious Education (PAI) has a strategic role in forming characters that are not only religious, but also able to live side by side harmoniously in society. The purpose of this study is to describe the integration of Islamic religious education with pluralism and multiculturalism and the role of Islamic religious education as an agent of positive change. This study uses a descriptive qualitative approach with a library research method analyzing various libraries and academic sources related to the integration of Islamic religious education (PAI) with pluralism and multiculturalism. Data sources in this study consist of secondary data in the form of books and journal articles that are relevant to the research and data analysis techniques using a qualitative approach. The results of the study indicate that the integration of Islamic religious education (PAI) with pluralism and multiculturalism through inclusive learning, interfaith dialogue, development of multicultural skills, teaching universal values, awareness of Human Rights, in-depth educator training is very important in forming an attitude of mutual respect, tolerance and appreciation of differences, so as to reduce exclusive, radical, and intolerant attitudes. The role of Islamic Religious Education as an agent of positive change includes the formation of individual character, Islamic Religious Education as an agent of social change, the role of Islamic Religious Education institutions. The conclusion of this writing is that the integration of Islamic Religious Education with pluralism and multiculturalism must be carried out holistically, wisely, and contextually to be relevant to the conditions of a diverse Indonesian society, and to be able to form a future generation that is tolerant and lives side by side harmoniously.